2010
DOI: 10.1021/ol102400c
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Incednam, the Aglycon of Incednine

Abstract: The first total synthesis of incednam (1), the aglycon of antibiotic incednine (2), is described. Incednine has been reported to exhibit significant inhibitory activity against the antiapoptotic oncoproteins Bcl-2 and Bcl-xL. The synthesis of 1 commenced with the preparation of the C1-C13 subunit 3 and the C14-C23 subunit 4. The construction of the novel 24-membered macrocycle was achieved by the application of a Stille coupling between 3 and 4, followed by macrolactamization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The relative configuration of the monosaccharides in 11 was determined based on coupling constants and NOEs analysis (Supplementary Figure 11 ). The absolute stereochemistry of the chiral centers in 11 was assumed to be identical to that reported for incednine ( Futamura et al, 2008 ; Ohtani et al, 2010 ) based on the key NOEs observed for 11 which turned out to be identical to those reported for incednine. Molecular modeling of 11 based on the reported models for incednine and incednam (its aglycon) ( Pérez-Victoria et al, 2016 ), perfectly match these key NOEs and confirms that the aglycon of 11 and incednam share the same absolute stereochemistry (Supplementary Figure 12 ).…”
Section: Resultsmentioning
confidence: 87%
“…The relative configuration of the monosaccharides in 11 was determined based on coupling constants and NOEs analysis (Supplementary Figure 11 ). The absolute stereochemistry of the chiral centers in 11 was assumed to be identical to that reported for incednine ( Futamura et al, 2008 ; Ohtani et al, 2010 ) based on the key NOEs observed for 11 which turned out to be identical to those reported for incednine. Molecular modeling of 11 based on the reported models for incednine and incednam (its aglycon) ( Pérez-Victoria et al, 2016 ), perfectly match these key NOEs and confirms that the aglycon of 11 and incednam share the same absolute stereochemistry (Supplementary Figure 12 ).…”
Section: Resultsmentioning
confidence: 87%
“…The initial total synthesis of 1 was accomplished by preparation of the C14-C23 subunit 4, which could not be stored and was used immediately for the next step due to the instability. 5 To circumvent this issue for the practical synthesis of 1, the retrosynthesis of 1 was redesigned via precursor 5 or 6 for intramolecular ring-closing olefin metathesis reaction [6][7][8] to construct the 24-membered macrocycle concomitant with the labile C14-C21 tetraene unit at a later stage in the synthesis. The new retrosynthetic analysis of 1 is depicted in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…1 H-NMR, 13 C-NMR, HRMS (ESI-TOF), and optical rotation data obtained for a sample of the synthetic incednam matched those of an authentic sample 1 and of a sample from the initial synthesis of 1. 5 In conclusion, a novel convergent synthetic route was developed for incednam (1), which is the aglycon of the 24-membered macrolactam glycoside antibiotic incednine (2), using intramolecular ring-closing olefin metathesis reaction as a key step. Although the yield of the intramolecular ring-closing olefin metathesis reaction was not extremely high, the present synthetic route avoids the use of unstable fragments, such as 4, in the total synthesis of 1.…”
Section: Synthesis Of Incednammentioning
confidence: 99%
See 1 more Smart Citation
“…With the two segments 6 and 7 in hand, we proceeded to the final stage of our synthesis of 4 (Scheme ). The coupling of 6 and 7 was conducted according to Corey’s modification of the Stille coupling reaction to give 19 in 89% yield . The product 19 was considered to be generated as a 1:1 diastereomeric mixture at the C2 stereocenter, although the diastereomers were indistinguishable both in 1 H and 13 C NMR spectra.…”
mentioning
confidence: 99%